Germline pathogenic variants in the MRE11, RAD50, and NBN (MRN) genes in cancer predisposition: A systematic review and meta-analysis - Stastna, Barbora; Dolezalova, Tatana; Matějková, Kateřina; Nemcova, Barbora; Zemankova, Petra; Janatova, Marketa; Kleiblova, Petra; Soukupova, Jana; Kleibl, Zdenek (International journal of cancer, 2024)
The MRE11, RAD50, and NBN genes encode the MRN complex sensing DNA breaks and directing their repair. While carriers of biallelic germline pathogenic variants (gPV) develop rare chromosomal instability syndromes, the cancer risk in heterozygotes remains controversial. We performed a systematic review and meta-analysis of 53 studies in patients with different cancer diagnoses to better understand the cancer risk. We found an increased risk (odds ratio, 95% confidence interval) for gPV carriers in NBN for melanoma (7.14; 3.30-15.43), pancreatic cancer (4.03; 2.14-7.58), hematological tumors (3.42; 1.14-10.22), and prostate cancer (2.44, 1.84-3.24), but a low risk for breast cancer (1.29; 1.00-1.66) and an insignificant risk for ovarian cancer (1.53; 0.76-3.09). We found no increased breast cancer risk in carriers of gPV in RAD50 (0.93; 0.74-1.16; except of c.687del carriers) and MRE11 (0.87; 0.66-1.13). The secondary burden analysis compared the frequencies of gPV in MRN genes in patients from 150 studies with those in the gnomAD database. In NBN gPV carriers, this analysis additionally showed a high risk for brain tumors (5.06; 2.39-9.52), a low risk for colorectal (1.64; 1.26-2.10) and hepatobiliary (2.16; 1.02-4.06) cancers, and no risk for endometrial, and gastric cancer. The secondary burden analysis showed also a moderate risk for ovarian cancer (3.00; 1.27-6.08) in MRE11 gPV carriers, and no risk for ovarian and hepatobiliary cancers in RAD50 gPV carriers. These findings provide a robust clinical evidence of cancer risks to guide personalized clinical management in heterozygous carriers of gPV in the MRE11, RAD50, and NBN genes.
Keywords: zárodečné mutace; Genetic Predisposition to Disease; Neoplasms; MRE11 Homologue Protein; hydrolasy působící na anhydridy kyselin; Acid Anhydride Hydrolases; jaderné proteiny; DNA vazebné proteiny; proteiny buněčného cyklu; Germ-Line Mutation; lidé; enzymy opravy DNA; ženské pohlaví; Humans; nádory; Female; homologní protein MRE11; Cell Cycle Proteins; Nuclear Proteins; DNA-Binding Proteins; DNA Repair Enzymes; genetická predispozice k nemoci